The Power of Political Discussion: Uncovering the Influence of Networks on Vote Choice and its Mechanisms: Evidence from Colombia - García Sánchez, Miguel; Botero, Felipe (Revista Latinoamericana de Opinión Pública, 2023)
This paper explores the influence of political discussion networks on vote choice. We ask two questions: What type of discussion networks influence vote choice? And, what are the mechanisms through which discussion networks influence voting behavior? We argue that discussing politics with others affects electoral decisions when citizens are surrounded by discussants whose political views are homogeneous and that this influence can operate through two mechanisms: information and social pressure. Using data from a two-wave panel study conducted in Bogotá before and after the 2011 local elections, we find evidence of the effects of social networks on voter behavior. The homogeneity of discussion networks is correlated with a change in vote choice, and this link appears to be driven both by information and social pressure.